Parenting Practices in Raising Children as Qur'an Memorizers: A Phenomenological Study of Senior Teachers at Al-Amien Prenduan Islamic Boarding School - Ferdiansyah; Fajrul Falah; Abd. Qadir Jailani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
In today's modern era, raising a generation of Qur'an memorizers has become increasingly challenging due to technological and social changes. This study aims to explore effective parenting practices in nurturing children as memorizers of the Qur'an based on the experiences of senior teachers at Al-Amien Prenduan Islamic Boarding School. Employing a phenomenological approach, data were collected through in-depth interviews with senior teachers who have extensive experience in guiding Qur'an memorizers.The findings indicate that successful parenting practices are not solely based on discipline but also on strong emotional bonds between parents and children. Moral support, continuous motivation, parental role modeling, and a supportive environment play significant roles in the memorization process. Despite challenges such as limited time and technological distractions, collaboration between parents and the Islamic boarding school contributes significantly to the development of children who are not only proficient in memorizing the Qur'an but also possess strong spiritual values and noble character.This study provides valuable insights for parents and educators in fostering future generations of Qur'an memorizers.